HUBUNGAN ANTARA LINGKUNGAN KELUARGA DAN MINAT BELAJAR MATEMATIKA SISWA SMP - Wasistha, Sondha Ken; Rikayanti, Rikayanti (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The family environment is very influential in the development of student learning outcomes. In the development of children, the family plays an important role in assisting the development of children in their education which includes obstacles or learning difficulties. The purpose of this study was (1) to evaluate whether there is a correlation between the family environment and students 'interest in studying mathematics and (2) this study was to measure the extent to which the role or contribution derived from the family environment in shaping students' interests. This research can be classified as quantitative research, which takes an approach using correlational methods. In other words, this study focuses on the analysis of relationships or correlations between certain variables in a research context. The sample used in this study consisted of 37 seventh grade students in one of the State Junior High School located in Karawang. The findings of the study indicate a positive correlation between the condition of the family environment and students ' interest in learning mathematics at the level of grade VII (GIS value. 0,000 0,05). Based on the results of correlation analysis, there is a calculated r value of 0.556, while the R value of the table is 0.32461. Thus, since the value of R count (0.556) is greater than that of R table (0.32461), it can be concluded that there is a positive correlation between the family environment and interest in learning mathematics. The family environment variable gave dedication to learning interest by 30.9% and another 69.1% came from other factors.